Real-Time and Accurate pH Sensor Based on Internet of Things (IoT) - Ikano, Robin; Setiawan, Dewa Gede Eka; Yunus, Muhammad; Demulawa, Meilan; Rahman, Irsan (Dewantara Journal of Technology, 2025)
One important parameter that needs to be considered in water quality is the acidity level (pH) in the water. This study aims to design and determine real-time and accurate pH sensor based on internet of thing (IoT). This system design uses an ESP32 microcontroller and The PH-4502C pH Meter Module sensor. The ESP32 can be connected to the IoT-based Blynk platform, allowing pH data to be monitored in real time via a smartphone. Testing of the IoT-based pH sensor was conducted to evaluate the system's real-time operation under varying distances. Meanwhile, the pH sensor's accuracy was determined by comparing its output with a digital pH meter using buffer solutions at different pH levels. The test results show that the time value required in each range is always constant, namely 1 s. This proves that IoT-based monitoring does not affect the range. Meanwhile, measurement of pH level was the average error value is 3.49%, and the sensor accuracy is 96.51%. These results indicate a low error rate, resulting in high accuracy. The sensor error value of 3.49% is lower than the specified error tolerance limit of <5%. This proves that the pH sensor, with an accuracy of 96.51%, is suitable and reliable for measuring pH in solutions.